War on heaven and earth: Misotheistic themes in popular culture. Issue 4 (16th September 2019) - Vainio, Olli‐Pekka
Abstract: In this article, I evaluate particular critical narratives of religion in pop culture. I note briefly some early cases where criticism is primarily directed at religious abuses. Next, I make some observations about the misotheistic tradition in which the relationship between religious reality and human life is more complicated. Finally, I make some remarks on the use of religious and quasireligious elements in pop culture and what kind of effects these might have on our social imagination.